2018
DOI: 10.1039/c7bm01182b
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-sensitive cytotoxic peptide–dendrimer conjugates enhance cell apoptosis and deep tumor penetration

Abstract: Peptide nanodrugs have been developed as promising antitumor chemotherapeutics because they partially overcome the drawbacks of free peptide drugs, but insufficient tumor penetration and interference of peptide function limit their further application. In this work, we have developed multifunctional peptide conjugated dendrimers for improving tumor penetration, cancer cell-specific peptide delivery and anticancer ability. The cytotoxic peptide KLAK, cell-penetrating peptide TAT and matrix metalloproteinase 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 68 publications
0
35
0
Order By: Relevance
“…For this reason, Liu and colleagues (2018) developed an acryl G4 PAMAM-NH 2 dendrimer conjugated to the cell-penetrating peptide, trans-activating transcriptional (TAT) activator peptide, along with PEG for delivery of the cytotoxic peptide (KLAKLAK) 2 (KLAK). 87 This conjugated dendrimer, denoted as PKT-S-PEG, was built according to a KLAK:TAT:PEG molar ratio of 50:10:40. KLAK is a peptide that specifically destroys the mitochondrial membrane of cells to elicit the apoptotic cascade for cell destruction.…”
Section: Tumor Penetrationmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, Liu and colleagues (2018) developed an acryl G4 PAMAM-NH 2 dendrimer conjugated to the cell-penetrating peptide, trans-activating transcriptional (TAT) activator peptide, along with PEG for delivery of the cytotoxic peptide (KLAKLAK) 2 (KLAK). 87 This conjugated dendrimer, denoted as PKT-S-PEG, was built according to a KLAK:TAT:PEG molar ratio of 50:10:40. KLAK is a peptide that specifically destroys the mitochondrial membrane of cells to elicit the apoptotic cascade for cell destruction.…”
Section: Tumor Penetrationmentioning
confidence: 99%
“…PKT-S-PEG dendrimers penetrated to a depth of 70-80 μm within the tumor with high fluorescence intensity in the tumor interior whereas control dendrimers penetrated down to 30 μm, only, after an 8 hr incubation. 87 The investigation by Liu and colleagues (2018) has demonstrated the importance of enhancing tumor penetration as large tumors can be difficult to eradicate effectively without appropriate depth of therapeutic intervention. 87…”
Section: Tumor Penetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The size shrinkage property benefits the cleaved dendrimers in the enhanced permeability and retention (EPR) effect, thus improving the cellular uptake of nanoparticles [ 132 , 133 ]. Liu et al also employed MMP2-sensitive peptide (GPLGIAGQ) in generation 4 PAMAM dendrimers for delivering cytotoxic peptide KLAK [ 118 ]. Unlike previous examples showing potential drawbacks in peptide-conjugated nanocarriers, Liu et al demonstrated the opposite proteolytic properties.…”
Section: Dendrimersmentioning
confidence: 99%
“…The generated structure allows for derivatization on terminal groups leading to a high density of various possible desired terminal modifications. This possibility has gained some interest especially in medical applications ranging from drug delivery39,40 and cytotoxica4143 to fluorescence imaging 44. Apart from the aforementioned applications, possible modifications with gadolinium have been reported 45,46.…”
Section: Introductionmentioning
confidence: 99%